Analisis Manajemen Mutu Sekolah Islam (Standar Kepegawaian dalam SOP SDIT Al-Uswah Surabaya) - Aris Nurbawani (Southeast Asian Journal of Islamic Education Management, 2023)
Many public elementary schools in Indonesia in the 2023 PPDB will not receive any students at all. Meanwhile, SDIT Al Uswah Surabaya is different, this school is one of the Islamic schools in Surabaya which always gets quite a lot of students every year. Quality is one of the factors that makes a school attractive. One quality is the suitability of a condition to the standards used, including the suitability of the human resource standards held by SDIT Al Uswah Surabaya. This research aims to analyze the Standard Operating Procedure (SOP) for staffing standards at SDIT Al Uswah Surabaya along with its advantages and disadvantages. This research uses a qualitative approach. This research uses secondary data. Data were analyzed using human resource management theory according to Schermerhorn. The results of this research show that the SOP for staffing standards at SDIT Al Uswah Surabaya consists of 25 SOPs. The quality workforce search function consists of one SOP, the quality workforce development function consists of five SOPs, and workforce maintenance consists of twenty SOPs, and there are two SOP that can be grouped into two human resource management functions at once. The advantage of the SDIT Al Uswah Surabaya SOP is that it is prepared simply so that it is easy to understand and implement. The weakness of the SDIT Al Uswah Surabaya SOP is that there is inequality in making SOPs, namely that the maintenance SOP has more SOPs than the SOP for workforce search and development.